Երաժշտական կրթության դերը երեխաների և դեռահասների կրեատիվության զարգացման հարցում - Գյանջումյան, Էդգար (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
В статье рассматривается роль музыкального образования в развитии креативности детей и подростков, a также некоторые особенности организации учебного процесса, способствующие развитию креативности. The article discusses the role of music education in the development of creativity in children and adolescents, as well as some peculiarities of organization of the educational process that promote the development of creativity.
Keywords: Երաժշտագիտություն